2012
DOI: 10.1097/mcg.0b013e318249c4b8
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-associated Gastric Carcinoma

Abstract: Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC) is a recently recognized entity, which is defined by the presence of EBV in the gastric carcinoma cells. EBVaGC represents about 10% of gastric carcinoma worldwide, and >80,000 patients are estimated to develop EBVaGC annually. EBVaGC shows some distinct clinicopathologic characteristics, such as male predominance, predisposition to the proximal stomach, and a high proportion in diffuse-type gastric carcinomas. Besides, EBVaGC also shows characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 113 publications
4
63
0
14
Order By: Relevance
“…In recent years, reports have been published suggesting a relationship between EBV and gastric cancer [19][20][21][22]. It has been reported that EBV is associated with 10% of gastric carcinomas and that in most cases positive EBV is diagnosed in poorly differentiated or moderately differentiated grades [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reports have been published suggesting a relationship between EBV and gastric cancer [19][20][21][22]. It has been reported that EBV is associated with 10% of gastric carcinomas and that in most cases positive EBV is diagnosed in poorly differentiated or moderately differentiated grades [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, DNA methylation is a basic physiological process in biological organisms, which transforms cytosine into 5'-methylcytosine using DNA methyltransferases (DNMTs). Therefore, DNA methylation serves an important role in maintaining chromatin structures, DNA conformation, DNA stability and DNA-protein interactions (5). However, abnormal methylation of DNA in certain pathological conditions may deactivate tumor suppressor genes and activate oncogenes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The GAC-EBV is a unique clinicopathological entity: it appears to be more prevalent in men, is usually found in the proximal region of the stomach and is frequently present in younger subjects [35,36]. A recent publication found PIK3CA mutations in about 80% of GAC-EBV [20], and papers have reported that GAC-EBV patients usually have less lymph node disease but with contradictory prognosis reports [35][36][37][38].…”
Section: The Investigation Of Exogenous Elementsmentioning
confidence: 99%